Pengembangan Media Permainan Lompat Kodok Portable dalam Pembelajaran Menghafal Doa Sehari-Hari di PAUD Rahayu Kota Bengkulu - Rezie Zilvia Utari; Nelly Marhayati; Fatrica Syafri; Alimni Alimni (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study employed a Research and Development (R&D) approach to develop a Portable Frog Jump Game as a learning medium for memorizing daily prayers among children aged 5–6 years at PAUD Rahayu, Bengkulu City. The study was motivated by the limited ability of young children to memorize daily prayers due to the lack of engaging and interactive learning media. During learning activities, children tended to lose focus and showed low interest in memorizing daily prayers. Therefore, an innovative learning medium integrating traditional games with religious and moral education was developed to enhance children's learning experiences. The study adopted the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Product validation was conducted by five experts specializing in instructional materials, language, educational media, educational technology, and early childhood education. The validation results indicated that the Portable Frog Jump Game learning media achieved a very high level of validity and was considered appropriate for classroom implementation. The implementation stage involved a field trial with 14 children aged 5–6 years at PAUD Rahayu, Bengkulu City. The findings demonstrate that the developed learning media is feasible for use in early childhood education and has the potential to support children's memorization of daily prayers through enjoyable and interactive learning activities.